2017
DOI: 10.1093/geronb/gbx127
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Work and Incident Cognitive Impairment in Puerto Rican Older Adults

Abstract: Complexity of work may reduce risk of cognitive impairment in Puerto Rican older adults, especially when combined with favorable childhood economic conditions and higher educational attainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…It appears that, in this specific cohort of Puerto Ricans born before 1943, education may be a more relevant factor for the rate of cognitive aging than the characteristics of work such as job strain. These results go along with the findings for work complexity and cognition in the PREHCO sample reported previously (Andel et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It appears that, in this specific cohort of Puerto Ricans born before 1943, education may be a more relevant factor for the rate of cognitive aging than the characteristics of work such as job strain. These results go along with the findings for work complexity and cognition in the PREHCO sample reported previously (Andel et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the job demand–control model and previous findings that low job control is associated with poorer cognitive functioning (Andel et al, 2011, 2015), we expected that low job control and high job strain (i.e., high ratio of job demands to job control) would relate to greater late-life cognitive decline in Puerto Rican older adults. Inline with previous work examining job strain and education as predictors of long-term health outcomes (Nilsen et al, 2014), as well as our study on work complexity and cognitive impairment in this sample (Andel et al, 2019), we also expected that education would have a major role in the association between job strain indicators and cognitive change.…”
Section: The Current Studysupporting
confidence: 62%
See 1 more Smart Citation
“…This line of research has been followed up recently in other cross-national research (e.g. by Gow and colleagues (2014) and by Andel et al (2019)), who found, in keeping with the Kohn studies, that workers involved in intellectually challenging occupations (as assessed by the workers themselves) scored higher in cognitive ability. Cross-national data from the EWCS have also documented a range of negative psychological and physical health outcomes that are associated with employment in jobs perceived to afford lower control or discretion in job performance and/or high job demands (Hakanen et al, 2019;Lorente et al, 2018;Nappo, 2019;Toch et al, 2014).…”
Section: Introductionmentioning
confidence: 66%
“…Early evidence suggested that occupation, together with education, plays a crucial role against the development of dementia 13 . This has been replicated in subsequent studies with large groups 12,14 . One critical aspect that has been poorly investigated in previous studies is when and how the different CR proxies have an effect.…”
Section: Introductionmentioning
confidence: 57%